Mga kagamitang panturo para sa isahang paglinang ng mga kasanayan sa pakikinig (aural discourse) ng mga mag-aaral sa unang taon ng mataas na paaralan - Pangilinan, Luisa Sunga 1937- (1978)
This seminar paper attempted to present the design and development phases in the preparation of aural discourse materials. A survey was made and examination of instructional materials currently available in Pilipino for first year high school students was done so as to have a valid justification for the design of a new set of materials. The experimental materials were subjected to an internal evaluation to determine the workability of the materials in actual classroom situations.